2017
DOI: 10.3319/tao.2017.02.17.01
|View full text |Cite
|
Sign up to set email alerts
|

The seismogenic process of the 2016 Meinong earthquake, southwest Taiwan

Abstract: Southwest (SW) Taiwan lies on the deformation front of a plate collision zone. Most earthquakes in this region occur due to deformation of the upper crust, therefore, potential seismic hazards in this area must be considered. On 6 February 2016, a moderate, but disastrous earthquake (M L = 6.6; depth = 14.6 km) occurred in Meinong, a district in the Kaohsiung area of Taiwan. This earthquake produced three cluster-like aftershocks. Among them, two of the aftershocks clusters were not spatially correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The used fault plane is different from the other studies. According to some researches (e.g., Jian et al, 2017;Kanamori et al, 2017;Lee et al, 2016;Lin et al, 2018;Wen et al, 2017), the fault plane of the 2016 Meinong earthquake was NW-SE striking and NE dipping with one or two asperities. Besides, from the waveform inversion alone, Kanamori et al (2017) proposed that they cannot determine which one of the two nodal planes was the real fault plane.…”
Section: Comparison Between This Study and Other Source Modelsmentioning
confidence: 99%
“…The used fault plane is different from the other studies. According to some researches (e.g., Jian et al, 2017;Kanamori et al, 2017;Lee et al, 2016;Lin et al, 2018;Wen et al, 2017), the fault plane of the 2016 Meinong earthquake was NW-SE striking and NE dipping with one or two asperities. Besides, from the waveform inversion alone, Kanamori et al (2017) proposed that they cannot determine which one of the two nodal planes was the real fault plane.…”
Section: Comparison Between This Study and Other Source Modelsmentioning
confidence: 99%
“…After the Meinong earthquake, Wen et al [37] relocated the aftershock catalog and indicated three clusters of aftershocks. The first cluster of aftershocks near the epicenter was 10-20 km in depth, then the second cluster was 5-10 km in depth and 10 km north of the hypocenter.…”
Section: Study Areamentioning
confidence: 99%
“…The insights of some potential activities of large earthquakes in the future are correlated with the relationships between Coulomb stress and the triggering of earthquakes [4][5][6][7]. The mainshock-aftershock interactions were concluded in 2013, Nantou earthquakes series [8] and 2016, Meinong earthquakes [9]. Recently, Li et al [10] investigated the earthquake interactions in the central Taiwan using the ∆CFSs effects driven from the past earthquakes (M L ≥ 5.5) from 1900 to 2017.…”
Section: Introductionmentioning
confidence: 99%